Gestão da informação no sistema de Processo Judicial Eletrônico (PJE) do Tribunal Regional do Trabalho - TRT 13ª Região - Diniz, Bárbara Carvalho (2020)
Knowing the strategic and organizational importance of information management in institutions and information systems, and considering that the judiciary must make decisions in an agile, effective and responsible manner, the objective is to analyze information management in the electronic Judicial Process System ( PJe) of the 13th Region Regional Labor Court (TRT), in order to: identify the information management process in the PJe System; verify the barriers and facilitating factors that help the flow and processing of information in the information management process; map the information needs of technical and judicial analysts and; propose guidelines based on theories of information management, management of digital archival documents and other reported needs. Methodologically, it is characterized as an exploratory and descriptive study, carried out through field and documentary research, with a qualitative and quantitative approach. Focused semi-structured interviews and systematic observation with 16 users (12 technicians, 3 analysts from the 13 courts, from the Maximiano Figueiredo Labor Forum (TRT 13ª Region), as well as a member of the Permanent Evaluation Commission, were used as data collection techniques. of TRT 13th Region Documents The results were analyzed by the collective subject discourse analysis method and pointed out that, for most users, the PJe system offers more agility, accessibility to information and improvement in the procedural flow and provides several resources that facilitate the search, retrieval, visualization and sharing of information, however, in the stages of insertion, storage, use, elimination and / or preservation, there are deficiencies, mainly with regard to the management of legal processes, considered as digital archival documents, not receiving proper treatment, which may harm in the near future. mo the GI process It is recommended to adopt and / or integrate a Computerized Archival Document Management System (SIGAD) and / or Trusted Digital Repository (RDC-Arq), as well as the use of the Access To Memory software (ICA -AtoM), to the PJe system. Considering the needs reported by users on information management, it is called for compliance with the document management process and information and archival policies, emphasizing that information technologies are one of the necessary instruments for information management, but not enough to promote effective, accessible and democratic management. It is concluded that the developers and managers of the system develop an environment of Technocratic Utopia, in which the use of technologies is of enormous value, but they despise informational and archival policies regarding information management. Knowing this, it is essential to comply with archival policies aimed at document management, with the use of specific software, as well as document evaluation through a permanent committee, so that there is management and preservation of information over time.